Internationalisation of non-financial social and solidarity economy cooperatives: case study in Ecuador - Mercedes Moreira-Menéndez; Roberto Pico-Saltos; Carlos Edison Zambrano (Future Business Journal)
Abstract Internationalisation is a way for companies' growth and economic development in transition economies with the potential to contribute to a more sustainable world. Social and solidarity economy cooperatives (SSECs) have a lower internationalisation trend than developed economy companies due to their aversion to possible economic losses and lack of knowledge of the global market. This study aims to propose an internationalisation model for non-financial SSECs through factor analysis and evolutionary genetic computing to improve structural competitiveness within the framework of sustainable development in an emerging country. The study methodology includes: (1) information analysis related to internationalisation indicators; (2) statistical analysis of variables from the national survey of popular and solidarity economy organisations; (3) internationalisation model through a genetic algorithm; and (4) strategies related to sustainability. The results show internationalisation models with significant indicators such as number of partners, social capital, social benefit, access to international markets and employment. These models have goodness of fit with a high degree of precision (> 80%) and are a novel proposal to estimate the internationalisation of social capital cooperatives.